A metrópole híbrida:o papel do turismo no processo de urbanização da Região Metropolitana de Fortaleza - Paiva, Ricardo Alexandre (2011)
This research investigates the role of tourism in the contemporary process of urbanization of Fortaleza Metropolitan Region, Ceará, Brazil, based on a comparative analysis between the process of production and consumption of space related to the industrial logic and to tourism. Based on the dialectical relationship between space and society, it presents the specific features of the uneven urbanization process occurred in the past, premise for understanding the impacts of socio-spatial tourism of sun and sea modality on the metropolitan territory. The relevance of the research is grounded in the need to question the role played by the State the inclusion of tourism, through public policies, actions and speeches, as a strategic activity in the process of social restructuring (economical, political and cultural-ideological) of Ceará, with the objective to include in the pattern of globalized production and consumption, reproducing the hegemonic interests and reflecting on new patterns of socio-spatial inequalities. The method is based on theoretical propositions, images and quantitative data to evaluate the peculiarities of tourism urbanization in Fortaleza Metropolitan Region, analyzing the process of structuring and metropolitan expansion, as well as the precarious urbanization caused by tourism; infrastructure interventions; impacts on the coast of Fortaleza and its metropolitan area; urban interventions through urban design and architecture and its relation to the construction of the tourist image of Fortaleza; the links between tourism and real estate market and the urban phenomenon of second home; spatial manifestations of the means of accommodation, especially resorts; and the relationship between tourism and environmental preservation. Although it has risen as the central hypothesis that the spatial changes triggered by social practices (economical, political and cultural-ideological) of tourism, were the hegemonic factor of recent urbanization of Fortaleza Metropolitan Region, it was concluded that old and new social dynamics (industrial, tertiary, real estate) contribute to this reality, when associated with tourism, it exacerbates the process of socio-spatial segregation and justifies the hybrid character of the contemporary process of “metropolization” of Fortaleza